APPLICATION OF PREGNANCY EXERCISES IN THE THIRD TRIMESTER TO REDUCE THE INTENSITY OF BACK PAIN IN PREGNANT WOMEN - Nurya Kumalasari; Desi Fitriana; Laily Himawati (LPPM AN Nuur, 2024)
Background : The most common discomfort experienced by pregnant women at 28 to 40 weeks of gestation (third trimester) is back pain. Starting from something trivial, back pain is often not a concern for pregnant women. Providing non-pharmacological therapy can be considered, for example, with pregnancy exercises to overcome the problem of back pain (Mongi, 2022). The purpose of community service in providing is to provide midwifery care for pregnancy with a focus on interventions for the application of pregnancy exercises in the third trimester to reduce back pain. Methodology : This community service activity involves providing pregnancy exercise training for 15-20 minutes in pregnancy classes. Results : Prenatal exercise given to pregnant women in the third trimester can have the effect of reducing discomfort, namely back pain, so that pregnant women can go through their pregnancy safely and comfortably. Conclusion : Improved health of pregnant women with a decrease in the scale of back pain after doing pregnancy exercises 4 times divided into 15 minute durations, with a frequency of 2 times per week, for 2 weeks